Coaxial power sensor calibration with adaptor by direct comparison transfer - Cai, Yang (2013)
This paper describes the practical development of National Metrology Centre (NMC)'s microwave power sensor calibration system using the direct comparison transfer method based on previous developed coaxial broadband calibration system. We propose an analytical method to deal with the adaptor problem to treat the connector difference and power level difference of DUTs from the reference standards. The model is established by using signal flow graph together with non-touching loop rule analyses. The calibration transfer equation is derived through the transfer functions. The uncertainties are evaluated for the complex reflection coefficient inputs following the internationally recommended guidelines.